Synthesis of Pyrido[3,2-c]coumarin Derivatives by an Intramolecular Cyclization of 4-Methyl-2-(ortho-methoxyphenyl)nicotinic Acid Using Eaton's Reagent - Tagawa, Yoshinobu; Yamagata, Kenji; Sumoto, Kunihiro (Letters in Organic Chemistry, 2006)
The reaction of 4-methyl-2-(methoxyphenyl)nicotinic acid with Eaton's reagent (P2O5 - CH3SO3H) affords pyrido[3,2-c]coumarin derivatives or 1-methyl-4-azafluoren-9-ones depending on the position of the methoxy group on the benzene ring.
Keywords: 1-methyl-4-azafluoren-9-one